Fabrication and Characterization of Nylon 6 Fiber via Wet Spinning Method for Application as a Reinforcing Material for a Direct Dental Bridge - Wijaya, Dissa Kirana; Djustiana, Nina; Faza, Yanwar; Cahyanto, Arief; Hardiansyah, Andri (UI Scholars Hub, 2023)
Nylon is a biocompatible thermoplastic polymer that is well known for its excellent fracture resistance, making it suitable for fabricating fiber-reinforced composite (FRC)-based dental bridges. FRC is widely used in dentistry. This study aimed to investigate the structural and morphological characteristics of the nylon 6 fiber prepared using five different weights of nylon 6 dissolved in formic acid. The nylon 6 fiber was successfully fabricated via a simple wet spinning method using water as a coagulant. The fiber was then characterized using Fourier transform infrared (FTIR) spectroscopy, optical microscopy, and scanning electron microscopy. FTIR spectroscopy confirmed the presence of nylon 6 characteristics in the fiber in the form of N–H and C=O groups at a specific wave number. The differences in the diameter and morphological shape of the fiber were attributed to the nylon 6 different concentrations. Furthermore, the nylon 6 fiber can be used to produce cost-effective products and realize suitable characteristics for use as an alternative to traditional materials for fabricating direct dental bridges.